A model to infer the demographic structure evolution of endangered donkey populations. (16th May 2017) - Navas, F. J.; Jordana, J.; León, J. M.; Barba, C.; Delgado, J. V.
Abstract : Stemming from The Worldwide Donkey Breeds Project, an initiative aiming at connecting international researchers and entities working with the donkey species, molecularly tested pedigree analyses were carried out to study the genetic diversity, structure and historical evolution of the Andalusian donkey breed since the 1980s to infer a model to study the situation of international endangered donkey breeds under the remarkably frequent unknown genetical background status behind them. Demographic and genetic variability parameters were evaluated using ENDOG (v4.8). Pedigree completeness and generation length were quantified for the four gametic pathways. Despite mean inbreeding was low, highly inbred animals were present in the pedigree. Average coancestry, relatedness, and non-random mating degree trends were computed. The effective population size based on individual inbreeding rate was about half when based on individual coancestry rate. Nei's distances and equivalent subpopulations number indicated differentiated farms in a highly structured population. Although genetic diversity loss since the founder generations could be considered small, intraherd breeding policies and the excessive contribution of few ancestors to the gene pool could lead to narrower pedigree bottlenecks. Long average generation intervals could be considered when reducing inbreeding. Wright's fixation statistics indicated slight inbreeding between farms. Pedigree shallowness suggested applying new breeding strategies to reliably estimate descriptive parameters and control the negative effects of inbreeding, which could indeed, mean the key to preserve such valuable animal resources avoiding the extinction they potentially head towards, making the present model become an international referent when assessing endangered donkey populations.